Biodegradable, Breathable Leaf Vein‐Based Tactile Sensors with Tunable Sensitivity and Sensing Range. Issue 8 (18th December 2021) - Liu, Yue; Tao, Juan; Yang, Wenkai; Zhang, Yufei; Li, Jing; Xie, Huilin; Bao, Rongrong; Gao, Wenchao; Pan, Caofeng
Abstract: Resistive pressure sensors have been widely studied for application in flexible wearable devices due to their outstanding pressure‐sensitive characteristics. In addition to the outstanding electrical performance, environmental friendliness, breathability, and wearable comfortability also deserve more attention. Here, a biodegradable, breathable multilayer pressure sensor based piezoresistive effect is presented. This pressure sensor is designed with all biodegradable materials, which show excellent biodegradability and breathability with a three‐dimensional porous hierarchical structure. Moreover, due to the multilayer structure, the contact area of the pressure sensitive layers is greatly increased and the loading pressure can be distributed to each layer, so the pressure sensor shows excellent pressure‐sensitive characteristics over a wide pressure sensing range (0.03–11.60 kPa) with a high sensitivity (6.33 kPa −1 ). Furthermore, the sensor is used as a human health monitoring equipment to monitor the human physiological signals and main joint movements, as well as be developed to detect different levels of pressure and further integrated into arrays for pressure imaging and a flexible musical keyboard. Considering the simple manufacturing process, the low cost, and the excellent performance, leaf vein‐based pressure sensors provide a good concept for environmentally friendly wearable devices. Abstract : Multilayered, biodegradable, breathable leaf vein‐based tactile sensors with customizable sensitivity, and linear sensing range are reported. The combination of the natural microstructure of the materials and the artificial multilayer structure improves the sensitivity and linear detection range of the tactile sensor, which provides a direction for the preparation of environmentally friendly and inexpensive electronic devices.